2021
DOI: 10.1016/j.ijans.2021.100341
|View full text |Cite
|
Sign up to set email alerts
|

The impact of psychological factors on bereavement among frontline nurses fighting Covid-19

Abstract: The COVID-19 pandemic has considerably changed the workplace and social relationships of nurses. As potential factors, uncertainty, stigma, and exposure of nurses' families to risk have disturbed the process of providing healthcare services for patients infected by COVID-19. Accordingly, this study aimed at determining the impact of psychological factors on stigma among frontline nurses fighting COVID-19. The extant paper was carried out based on the descriptive-analytical method for April-June 2020. A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…A recent study performed on Iranian nurses involved in the care of COVID-19 patients showed moderate levels of negative correlations between hardiness and stress, and a positive correlation with mental health (Pearson correlation coefficient −0.581, p < 0.05 and 0.474, p < 0.01, respectively) [47]. Similar results were found by Park et al on 187 nurses in a South Korean Hospital during the MERS virus outbreak in 2015 (Pearson's coefficients −0.401, p < 0.001 and 0.439, p < 0.001, respectively) [24].…”
Section: Discussionmentioning
confidence: 96%
“…A recent study performed on Iranian nurses involved in the care of COVID-19 patients showed moderate levels of negative correlations between hardiness and stress, and a positive correlation with mental health (Pearson correlation coefficient −0.581, p < 0.05 and 0.474, p < 0.01, respectively) [47]. Similar results were found by Park et al on 187 nurses in a South Korean Hospital during the MERS virus outbreak in 2015 (Pearson's coefficients −0.401, p < 0.001 and 0.439, p < 0.001, respectively) [24].…”
Section: Discussionmentioning
confidence: 96%
“…Caregivers on the front line of COVID-19 are susceptible to various mental illnesses due to the risk of being exposed to the virus. There are also concerns about infection and lack of personal protective equipment ( Azizpour et al, 2021 ). A cross-sectional study conducted on the medical personnel in China showed that among 512 personnel, about 164 personnel (32.03%) had direct contact with a patient infected with COVID-19, and the prevalence of anxiety was 12.5% (C.-Y.…”
Section: Introductionmentioning
confidence: 99%
“…One of the psychological and social consequences of contracting some diseases, especially infectious diseases in any society and in these difficult days of the spread of the Corona virus, is the patient’s fear of social reactions, the stigma of the disease and being a transmission agent. The current outbreak of the COVID-19 disease has caused stigma and discriminatory social behaviours against carriers and infected people ( Azizpour et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%